2015
DOI: 10.1016/j.phrp.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal and Oviposition Deterrent Activities of Medicinal Plant Extracts Against Aedes aegypti L. and Culex quinquefasciatus Say Mosquitoes (Diptera: Culicidae)

Abstract: ObjectivesTo evaluate the ovicidal and oviposition deterrent activities of five medicinal plant extracts namely Aegle marmelos (Linn.), Limonia acidissima (Linn.), Sphaeranthus indicus (Linn.), Sphaeranthus amaranthoides (burm.f), and Chromolaena odorata (Linn.) against Culex quinquefasciatus and Aedes aegypti mosquitoes. Three solvents, namely hexane, ethyl acetate, and methanol, were used for the preparation of extracts from each plant.MethodsFour different concentrations—62.5 parts per million (ppm), 125 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Mosquitoes are medically important insects and are considered as major public health pests as they transmit many dreadful diseases to humans and other warm blooded vertebrates [1]. Aedes aegypti and Culex quinquefasciatus are two important mosquito species under Culicidae family which transmit different diseases like dengue, yellow fever, chikungunya, Japanese encephalitis, and filariasis etc.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes are medically important insects and are considered as major public health pests as they transmit many dreadful diseases to humans and other warm blooded vertebrates [1]. Aedes aegypti and Culex quinquefasciatus are two important mosquito species under Culicidae family which transmit different diseases like dengue, yellow fever, chikungunya, Japanese encephalitis, and filariasis etc.…”
Section: Introductionmentioning
confidence: 99%
“…The WSMoL lectin from Moringa oleifera aqueous seed extract tested against A. aegypti eggs showed an EC 50 of 0.10 mg/ml, while the aqueous seed extract and its 0-60 protein fraction achieved EC 50 values of 0.32 and 0.16 mg/ml, respectively (de Santos et al 2012). The protolimonoid niloticin from the hexane leaf extract of Limonia acidissima was an excellent ovicidal against A. aegypti, since it showed 83.2 % ovicidal activity at 2 ppm concentration 120 h post-treatment (Reegan et al 2014), while 500 ppm of the hexane leaf extract of Limonia acidissima led to egg mortality of 60 and 79.2 % against A. aegypti and C. quinquefasciatus, respectively (Reegan et al 2015). Piperitenone oxide from Mentha spicata var.…”
Section: Botanical-based Mosquito Ovicidesmentioning
confidence: 99%
“…Antifeedant activity was found for extracts of Chrysanthemum sp. and Achillea millefolium L. against Spodoptera littoralis (Boisduval) and Pieris rapae L., respectively [17, 18], and plant extracts have also been found to act as an oviposition deterrent; Reegan et al [19] reported that a hexane extract of Limonia acidissima (L.) showed 100% oviposition deterrency for adults females of Culex quinquefasciatus Say and Aedes aegypti L.…”
Section: Introductionmentioning
confidence: 99%